1993
DOI: 10.1002/jbm.820270503
|View full text |Cite
|
Sign up to set email alerts
|

Improved cortical histology after cementation with a new MMA‐DMA‐IBMA bone cement: An animal study

Abstract: The histological response of bone to inert bone wax, conventional polymethylmethacrylate (PMMA), and a new formulation of bone cement, methylmethacrylate/n-decylmethacrylate/isobornylmethacrylate (MMA/DMA/IBMA) was investigated in canine tibial diaphysis. The new formulation of cement is characterized by a reduced exothermic temperature at curing and reduced leakage of chemicals to the adjacent bone. In comparison with bone wax, the MMA/DMA/IBMA bone cement did not differ significantly with respect to perioste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Boneloc cement was introduced in Norway in 1991, and became popular because of its asserted lower toxicity, low temperature rise during setting and its closed system for application (Jensen et al 1991, Nimb et al 1993, Kindt-Larsen et al 1995. It had 14% of the market for bone cement in Norway in 1992 (Annual Report 1996, The Norwegian Arthroplasty Register, Norway).…”
Section: Discussionmentioning
confidence: 99%
“…Boneloc cement was introduced in Norway in 1991, and became popular because of its asserted lower toxicity, low temperature rise during setting and its closed system for application (Jensen et al 1991, Nimb et al 1993, Kindt-Larsen et al 1995. It had 14% of the market for bone cement in Norway in 1992 (Annual Report 1996, The Norwegian Arthroplasty Register, Norway).…”
Section: Discussionmentioning
confidence: 99%
“…In the canine tibia, higher percentage of osteoid formation, less dead bone and less formation of fibrous tissue have been found after injection of MMA/ DMMBMA cement into the medullary cavity (Nimb et al 1993). In our study significant subsidence of the femoral cement mantle was only observed in the Bonelo@ group (2 cases, Table 4) questioning the clinical relevance of this finding.…”
Section: Discussionmentioning
confidence: 99%
“…A new bone cement, Bonel o@' , was developed to reduce the leakage of chemicals and the curing temperature. In a canine model, this cement was found to diminish bone necrosis and bone remodeling (Nimb et al 1993). …”
mentioning
confidence: 99%
“…Boneloc R cement was marketed without any clinical documentation. We began using it for routine total hip replacements (THR) in February 1992 because there was promise of it being less toxic [6,12,15], it would be easier to handle, polymer leakage into the air was reduced because of an integrated mixing system [2,7,12], and it had a lower polymerisation temperature than our usual cement (Palacos R ) [12].…”
Section: Introductionmentioning
confidence: 99%